2017
DOI: 10.1158/1535-7163.mct-16-0290
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and Functional Significance of RECQL1 Helicase in Sporadic Breast Cancers

Abstract: RECQL1, a key member of the RecQ family of DNA helicases, is required for DNA replication and DNA repair. Two recent studies have shown that germ-line RECQL1 mutations are associated with increased breast cancer susceptibility. Whether altered RECQL1 expression has clinicopathological significance in sporadic breast cancers is unknown. We evaluated RECQL1 at the transcriptomic level [METABRIC cohort, n=1977] and at the protein level [cohort 1, n=897; cohort 2, n= 252; cohort 3 (BRCA-germline deficient), n=74].… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 42 publications
3
29
0
Order By: Relevance
“…Overall, increased accumulation and transactivation of p53, and increased double strand breaks are consistent with the observed sensitivity of RECQ1-deficienct cells to MMS as shown here and doxorubicin as recently reported [ 47 ].…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Overall, increased accumulation and transactivation of p53, and increased double strand breaks are consistent with the observed sensitivity of RECQ1-deficienct cells to MMS as shown here and doxorubicin as recently reported [ 47 ].…”
Section: Resultssupporting
confidence: 92%
“…Analysis of TCGA data shows significant association of RECQ1 alterations with p53 mutation ( p < 0.001). Similarly, RECQ1 alterations exhibit significant tendency to co-occur with p53 mutations in METABRIC cohort of breast cancer patients where RECQ1 expression is correlated with patient survival [ 47 ]. To investigate whether RECQ1 mRNA expression predicts response to chemotherapy, we explored a large gene expression data set of 3951 human breast tumors ( http://kmplot.com/analysis/index.php?p=service&default=true ) [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using these optimised IHC conditions, we proceeded to investigate CDK18 protein expression in the Nottingham Tenovus series of 1650 breast cancers for which detailed clinicopathological parameters and various molecular markers have been previously defined [ 18 21 ]. Similar to the commercial breast cancer TMAs, we observed nuclear as well as cytoplasmic staining of CDK18, however, nuclear expression was rare and cytoplasmic expression was more common within these samples (Figure 2A ).…”
Section: Resultsmentioning
confidence: 99%
“…About prognostic studies, there was only one study evaluating the correlation of RECQL expression and survival in breast cancer from England population. Aroraet et al reported that the low level of RECQL expression was associated with poorer survival than did those with high level expression [ 27 ]. By extending their findings, we could demonstrate that RECQL expression was strongly associated with worse DRFS and DSS in Chinese women with breast cancer.…”
Section: Discussionmentioning
confidence: 99%